The kayon ideal shape: mathematical aesthetic on the kayon figures - Pandu Pramudita; Sarwanto Sarwanto; Soetarno Soetarno; Dendi Pratama (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The kayon figure is a traditional artefact in the shadow puppet form, which has features in its shape, so this figure is often utilized as the basis for a branding design to give an Indonesian identity. However, the kayon shape does not have enough explanation to be recognized as a geometric shape. This makes some people have an ethnocentric stigma against this figure utilizes. This research aims to explain the kayon shape using mathematical aesthetics to obtain objective results. The golden ratio with experimental methods is the theory to analyze the kayon shape. The structure and size data of kayon shapes were obtained from observing 25 kayon figure artefacts of Surakarta-style shadow puppets. The main structure of the kayon figure consists of the pucukan (the top part), the genukan-lengkeh (the middle part), and the palemahan (the bottom part). The kayon shape size ratio guide is obtained from the phi value in the golden ratio number pair with the formula φ1<n=φ2. The engineering drawing of kayon shape is carried out in three steps, consisting of the base grid system, the base layout kayon, and the kayon shape outline. This study concludes that the kayon ideal form is created from a 13:7 ratio. The contribution of this research is useful to be the basis for determining the aesthetics of kayon figures (wanda kayon), as a guide for the creation of kayon figures, and as an academic appreciation that the kayon shape is a geometric shape originating from Indonesia